PENELUSURAN TRANSFORMASI BENTUK ARSITEKTUR TRADISIONAL RUMAH ADAT KARAMPUANG - Meldawati Meldawati; Lottong Lottong (Journal Techno Entrepreneur Acta, 2016)
Changes in lifestyle, culture, religion, climate change and natural disasters because traditional homes are considered no longer able to accommodate the needs of its inhabitants. Karampuang customs area is the name of a village located +35 kilometers west of the district capital Sinjai South Sulawesi Indonesia, which has a history of birth "To Manurunge" on top of a hill known as Batu Lappa. This research emphasis on (1) identifying the basic morphological characteristics of traditional houses Karampuang accordance with the transformation of its shape (2) designing the time line of the history of the transformation of traditional forms of home and area Karampuang. When the study for 6 months with the sampling technique is a technique that samples purposive direct appointment by the researcher. Determination of case studies based on data from literature, interviews and field surveys. While data analysis technique descriptive analysis. Transformation of the traditional house Karampuang experienced three changes of shape and location of this was due to the development of confidence and dislocations that follows the water level at that time.